Potential returns to yam research investment in sub-Saharan Africa and beyond. (September 2020) - Mignouna, Djana Babatima; Akinola, Adebayo Akinboye; Abdoulaye, Tahirou; Alene, Arega D; Manyong, Victor; Maroya, Norbert G; Aighewi, Beatrice Anim; Kumar, Lava P; Balogun, Morufat; Lopez-Montes, Antonio; Rees, Deborah; Asiedu, Robert
Lack of good-quality planting materials has been identified as the most severe problem militating against increased agricultural productivity in sub-Saharan Africa (SSA) and beyond. However, investment of research efforts and resources in addressing this menace will only be feasible and worthwhile if attendant economic gains are considerable. As a way of investigating the economic viability of yam investment, this research has been initiated to address problems confronting yam productivity in eight countries of SSA and beyond: Nigeria, Ghana, Benin, Togo, Côte d'Ivoire, Papua New Guinea, Jamaica, and Columbia. Research options developed were to be deployed and disseminated. Key technologies include the adaptive yam minisett technique (AYMT), varieties adapted to low soil fertility and drought, nematode-resistant cultivars (NRC), and crop management and postharvest practices (CMPP). This article aims at estimating the potential economic returns, the expected number of beneficiaries, and poverty reduction consequent to the adoption of technology options. Estimates show that the new land area that will be covered by the technologies in the eight countries will range between 770, 000 ha and 1, 000, 000 ha with the highest quota accounted for by AYMT. The net present value will range between US584 and US1392 million and was highest for the NRC. The CMPP had the lowest benefit-cost ratio of 7.74. About 1, 049, 000 people would be moved out of poverty by these technologies by 2037 in the region. These technologies are less responsive to changes in cost than that in adoption rate. Therefore, the realization of the potential economic gains depends on the rate and extent of adoption of these technologies. Giving the knowledge-intensive nature of some of these interventions, capacity building of potential adopters will be critical to increasing the sustainability of the yam sector, thereby enhancing food security and reducing poverty.